Volume measurement of mango using acoustic resonance technique - Puttipipatkajorn, Amorndej (Engineering and Applied Science Research, 2014)
The objective of this research was to study and develop equipment to measure the volume of mango based on a technical acoustic resonance technique, namely that the resonance frequency that occurs in a Helmholtz resonator varies with the volume of air in the resonator. This method was used to measure nondestructively the volume of mango. The equation for volume prediction was derived from experiments by using different sizes and positions of mangoes. The prediction equation was a linear relationship between the volume of the mango and the resonance frequency. In addition, the experimental results showed that the standard error of prediction was 9.41 and the bias was -11.59 cm3